ANALISIS SEKTOR-SEKTOR UNGGULAN DALAM MENGGERAKKAN SEKTOR RIIL - Woroutami, Arti Dyah (Badan kebijakan Fiskal, 2010)
External fluctuation happened on global economy could be anticipated by Indonesia Government through a good coordination between fiscal and monetary policy. It is reflected from the Indonesia's positive economic growth on 2009 which reached 4,5 percent. But Indonesia's economic growth acceleration still retained by the low activity on real sector, so worried about the creation ofsustainable economic growth. Regarding that, it needs priority sharpening for sectors which has superiority on motivating the economy.To answer the problem, this article seek to identify business sectors which has superiority within economy and to formulate the policy needed to develop those sectors. The analysis is done by using Input Output table with baclcward linkage and forward linkage approach. Because of the limited data source, the analysis only from year 2000 until 2005.The output shows that there are 6 (six) sectors which has superiority within economy, that is Chemical Industry, Pesticide Fertilizer Industiy, Other Food industry, Rubber and Pesticide Industry, All-kind of Flour Industry, and Water, Gas and Electricity. For those superior sectors needs to be done a priority program thorugh budget spending policy.